Recombinant DNA and genetic experimentation : proceedings of a conference on recombinant DNA - Morgan, Joan; Whelan, W. J. (William Joseph) (Published for COGENE by Pergamon Press, 1979)
Recombinant DNA and Genetic Experimentation.